Strategi Peningkatan Prestasi Provinsi Nusa Tenggara Barat Pada Pekan Olahraga Nasional Ke-20 Di Papua - S, M. Ariy Dermawna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The West Nusa Tenggara government in 2021 participate in a national event, namely the National Sports Week (PON) in Papua. This participation encourages the regions to get proud achievements. For this reason, the West Nusa Tenggara government has made a strategy in dealing with the 2021 National Sports Week in Papua. The purpose of this study is to provide an overview of the strategies used by the NTB regional government in dealing with the Papua PON 2021. This type of research is a descriptive study with a qualitative approach to explain the NTB regional government's strategy to improve performance at the 2021 National Sports Week in Papua. The results showed that the strategy taken by the NTB government was successful in improving regional sports performance. These strategies include the regional training center (puslatda), the use of professional sports equipment, and increasing the number of the reward of the medal winners. NTB's achievement at the Papua PON 2021 is by winning 15 gold, 11 silver and 12 bronze. In terms of standings, it is ranked ninth nationally, where with this result is a new history for the Province of West Nusa Tenggara.